THE DEVELOPMENT OF AN OPEN-ENDED APPROACH BASED ON MEANINGFUL LEARNING IN SOCIAL STUDIES TO IMPROVE THE CRITICAL THINKING ABILITY - Ahsan Sofyan (Indonesian Journal of Learning and Instruction)
Abstract: This research aims to see the implementation of open-ended approach based on meaningful learning in social studies to improve the critical thinking skills of elementary school students Ausubel's open-ended learning model is very appropriate to be applied to improve students' critical thinking ability, and this is following the objectives of the open-ended approach based on meaningful learning. The formulation of the problem in this study is how to develop, implement, and influence and impact of the application of the open-ended approach on social studies learning to improve students' critical thinking ability. The method used is research and development. The study sites are four elementary schools in Tarakan City, while the subjects of this study are teachers and high-class students (grades 4,5 and 6) using purposive sampling technique. The results of this study indicate this approach is appropriate to use based on the assessment of peers, expert lecturers, and teachers, effectively improving students' critical thinking skills seen from the application during the learning process that is the average value of the experimental class students is higher by 83.33 than the average control class students an average of 80.07 in the final model validation test. It can be concluded that open-ended learning model based on meaningful learning in social studies learning to improve students' critical thinking skills in the City of Tarakan can effectively improve the critical thinking skills of Primary School students in the City of Tarakan. Keywords: Open-ended approach based on meaningful learning; social studies learning; critical thinking ability.